Iliopsoas pathology after total hip arthroplasty: a young person's complication. (1st February 2021) - Howell, Matthew; Rae, Fraser J.; Khan, Aman; Holt, Graeme
Abstract : Aims: Iliopsoas pathology is a relatively uncommon cause of pain following total hip arthroplasty (THA), typically presenting with symptoms of groin pain on active flexion and/or extension of the hip. A variety of conservative and surgical treatment options have been reported. In this retrospective cohort study, we report the incidence of iliopsoas pathology and treatment outcomes. Methods: A retrospective review of 1, 000 patients who underwent THA over a five-year period was conducted, to determine the incidence of patients diagnosed with iliopsoas pathology. Outcome following non-surgical and surgical management was assessed. Results: In all, 24 patients were diagnosed as having developed symptomatic iliopsoas pathology giving an incidence of 2.4%. While the mean age for receiving a THA was 65 years, the mean age for developing iliopsoas pathology was 54 years (28 to 67). Younger patients and those receiving THA for conditions other than primary osteoarthritis were at a higher risk of developing this complication. Ultrasound-guided steroid injection/physiotherapy resulted in complete resolution of symptoms in 61% of cases, partial resolution in 13%, and no benefit in 26%. Eight out of 24 patients (who initially responded to injection) subsequently underwent surgical intervention including tenotomy (n = 7) and revision of the acetabular component (n = 1). Conclusion: This is the largest case series to estimate the incidence of iliopsoas pathology to date. There is a higher incidence of this condition in younger patients, possibly due to the differing surgical indications. Arthoplasty for Perthes' disease or developmental dysplasia of the hip (DDH) often results in leg length and horizontal offset being increased. This, in turn, may increase tension on the iliopsoas tendon, possibly resulting in a higher risk of psoas irritation. Image-guided steroid injection is a low-risk, relatively effective treatment. In refractory cases, tendon release may be considered. Patients should be counselled of the risk of persisting groin pain when undergoing THA. Cite this article: Bone Joint J 2021;103-B(2):305–308.